150 million years of freshwater fish biogeography: vicariance or dispersal? - Cavin, Lionel (Food Agricultural Sciences and Technology, 2023)
Freshwater fishes are supposedly good case studies to test palaeobiogeographical models because they are attached to land masses, at least primary freshwater fishes, which are unable to cross marine barriers. In this study, I review the literature about the fossil record and about the phylogeny of various freshwater fish groups in order to address, in a qualitative way, the biogeographic scenarios proposed to explain their modern distribution. At the intercontinental scale, vicariant events seem to have played a minor role in the distribution of main freshwater fish clades, except for some during the first phases of the break-up. Most of the biogeographical events that shaped the modern distribution of freshwater fish clades are likely dispersals events that occurred in the Late Cretaceous and in the Palaeogene.